Synthesis and characterization of Fe3O4-NH2 and Fe3O4-NH2-chitosan nanoparticles - Silveira, M. L.D.C. [UNESP]; Silva, I. M.B. [UNESP]; Magdalena, A. G. [UNESP] (FapUNIFESP (SciELO), 2021)
Fe3O4nanoparticles were synthesized and functionalized with (3-aminopropyl) trimethoxysilane (APTMS) and chitosan, forming Fe3O4-NH2 and Fe3O4-NH2-chitosan nanoparticles. The Fe3O4nanoparticles were synthesized by a co-precipitation method and functionalization was performed in further stages. The nanoparticles were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), zeta potential, and transmission electron microscopy (TEM). The results of XRD showed that magnetite did not experience an oxidation reaction. The functionalization of the surface of Fe3O4nanoparticles was confirmed by FTIR and zeta potential measurements. The TEM results showed a thin layer around Fe3O4nanoparticles due to the functionalization with the APTMS. The later functionalization by chitosan contributed to the agglomeration of nanoparticles. Functionalization provided the nanoparticles better colloidal stability mainly for a pH below 7 and this improvement was related to the protection and new functional groups from the APTMS and chitosan.
Keywords: Functionalization; Nanoparticles; Surface modification